BEYOND DETERMINISTIC MODELS: PROBABILISTIC APPROACHES TO RISK-AWARE CIVIL ENGINEERING SYSTEMS - Joni Wilson Sitopu; Virgo Erlando Purba; Dermina Roni Santika Damanik; Sarah Williams (Journal of Moeslim Research Technik, 2026)
Civil engineering systems increasingly operate under conditions of uncertainty, variability, and exposure to extreme events, challenging the adequacy of deterministic modeling approaches that rely on fixed assumptions and simplified safety margins. Probabilistic methods offer a more realistic representation by explicitly incorporating uncertainty into analysis and decision-making processes. This study aims to develop a risk-aware probabilistic framework that enhances reliability assessment and supports more informed engineering decisions. A mixed-methods computational design was employed, integrating stochastic modeling, Monte Carlo simulation, Bayesian updating, and reliability analysis across representative infrastructure systems. Results indicate that probabilistic and hybrid models achieve higher reliability indices, lower probabilities of failure, and reduced expected losses compared to deterministic approaches. Statistical analysis confirms significant differences in performance, while case-based validation demonstrates strong agreement between probabilistic predictions and observed system behavior. Findings further reveal that adaptive integration of data-driven techniques improves model accuracy and responsiveness under dynamic conditions. This study concludes that probabilistic approaches provide a robust and scalable paradigm for risk-aware civil engineering, offering substantial implications for infrastructure design, maintenance, and resilience planning.